Effects of empowerment program on the burden of care in mothers of children with phenylketonuria - Rahgoi, Abolfazl; Sojoodi, Tahere; Fallahi Khoshknab, Masoud; Rahgozar, Mehdi; Shahshahani, Soheila (Iranian Journal of Child Neurology, 2019)
Objectives: Phenylketonuria (PKU) is a genetic disease of children that need a lifelong diet for its treatment. Because of the high burden of care, Parents and particularly mothers are prone to mental disorders or psychiatric adverse reactions. This study aimed to investigate the effect of empowerment of mothers on the burden of caring children with phenylketonuria. Materials & Methods: This was a semi-experimental (before-after with control group) study. In this research, 50 mothers of children with phenylketonuria that were referred to endocrine clinic in Qods hospital of Qazvin city, were selected and randomly divided into intervention and control groups. Data collection was made by using demographic characteristics of mothers and children and also the Zarit burden interview questionnaires. Empowerment program was delivered during nine sessions of holistic and family oriented empowerment model in the intervention group. The control group received routine services. Data were analyzed using descriptive and inferential statistics through SPSS software version 18. Results: In intervention group, the mean score of overall care burden and its dimensions in the mothers of children with phenylketonuria in post-test was significantly lower than the pre-test (41.20 ± 5.04 vs. 58.24 ± 3.96; p<0. 001); but pre-test and post-test scores in the control group had no significant difference (58.4 ± 5.22 vs. 58.96 ± 4; p=0.327). In other words empowerment program was able to reduce the burden of caring in mothers. Conclusion: Empowerment program can reduce the burden of care in mothers of children with phenylketonuria. Thus it seems that empowerment training is necessary to this group of mothers in the form of workshops and educational pamphlets.